Blind Dog Canyon : a Widowmaker Jones western - Cogburn, Brett (Cogburn, Brett. Widowmaker Jones western., 2023)
Hired to guard a silver claim in the Colorado mountains, Newt "The Widowmaker" Jones is targeted by Kirby Cutter, a cold-blooded killer whose hatchet man is an outlaw with a thirst for vengeance, while dealing with a crazed grizzly that has developed a taste for human flesh.